DRC: Reinstating executions shows a callous disregard for human rights - Amnesty International (Amnesty International, 2024)
Congo’s government wants to resume executions, after a hiatus of two decades, in a bid to combat armed groups and gang violence, Tigere Chagutah, Amnesty International’s Regional Director for East and Southern Africa, said:
Democratic Republic of the Congo

Spyware ruling a welcome step towards accountability for those targeted with NSO spyware - Amnesty International (Amnesty International, 2024)
A US district court has ordered Israeli spyware firm NSO Group to disclose documents and code related to its notorious Pegasus spyware, to WhatsApp.
United States of America

Spyware ruling a welcome step towards accountability for those targeted with NSO spyware - Amnesty International (Amnesty International, 2024)
The Amnesty International Security Lab has documented the massive scale and breadth of the use of Pegasus against human rights defenders and journalists across the world. It is vital that targets of Pegasus find out who has purchased and deployed the spyware against them so that they can seek meaningful redress.
United States of America

#Keepiton Sudan's internet shutdown threatens delivery of humanitarian and emergency services. - Amnesty International (Amnesty International, 2024)
A near total communication blackout in Sudan following all network and internet shutdowns in early February poses serious risks to the coordination of emergency assistance and humanitarian services to millions of people caught up in the conflict.
Sudan